A Wearable Microneedle‐Based Extended Gate Transistor for Real‐Time Detection of Sodium in Interstitial Fluids. Issue 10 (20th January 2022) - Zheng, Youbin; Omar, Rawan; Zhang, Rongjun; Tang, Ning; Khatib, Muhammad; Xu, Qi; Milyutin, Yana; Saliba, Walaa; Broza, Yoav Y.; Wu, Weiwei; Yuan, Miaomiao; Haick, Hossam
Abstract: Sodium is a prominent prognostic biomarker for assessing health status, such as dysnatremia. As of now, detection and monitoring of sodium levels in the human body is carried out by means of laborious and bulky laboratory equipmentand/or by offline analysis of various body fluids. Herein, an innovative stretchable, skin‐conformal and fast‐response microneedle extended‐gate FET biosensor is reported for real‐time detection of sodium in interstitial fluids for minimally invasive health monitoring along with high sensitivity, low limit of detection, excellent biocompatibility, and on‐body mechanical stability. The integration of the reported device with a wireless‐data transmitter and the Internet‐of‐Things cloud for real‐time monitoring and long‐term analysis is reported and discussed. This platform would eventually help bringing unlimited possibilities for effecient medical care and accurate clinical decision‐making. Abstract : A stretchable microneedle‐based extended gate field effect transistor for minimally invasive detection of sodium in the interstitial fluids and for real‐time health monitoring is reported. The device exhibits excellent biocompatibility, and on‐body mechanical stability and enables transfer of data via Internet‐of‐Things platforms.